Social work practice with immigrants and refugees - Balgopal, Pallassana R. (Foundations of social work knowledge., 2000)
The United States has always been a land of immigrants and a destination for refugees. With the increase in immigration in the late 1980s--when the number of refugees entering the United States nearly doubled as well--the number of clients needing social work services rose dramatically. Social Work Practice with Immigrants and Refugees takes an ecological systems perspective on working with these two distinct groups, paying special attention to the relationship between individuals and their social environment. Focusing on the major immigrant groups who have come to the United States since the 1965 Immigration Act, the book contains chapters on immigrants and refugees from Asia, Latin America, Europe, and Africa. Pallassana R. Balgopal and contributors explore ideas, concepts, and skills that will help human service workers, social workers, helping professionals, and policymakers deepen their understanding of cultural attitudes toward newly arrived immigrants and refugees, thus strengthening their ability to better serve an ethnically diverse clientele.